2010
DOI: 10.1002/ana.21950
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and risk of stroke among Chinese men and women

Abstract: Objective The relationship between body mass index (BMI) and stroke incidence and mortality remains controversial, particularly in Asian populations. Methods We conducted a prospective cohort study in a nationally representative sample of 169,871 Chinese men and women age 40 years or older. Data on body weight was obtained at baseline examination in 1991 using a standard protocol. Follow-up evaluation was conducted in 1999 to 2000, with a response rate of 93.4%. Results After excluding those participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 31 publications
7
103
2
2
Order By: Relevance
“…Some cohort studies have shown an increased risk of total stroke or ischemic stroke with elevating BMI, [8][9][10][11][12][13][14] which is in accord with the findings of the risk of ischemic stroke in our male subjects. On the other hand, other studies have found no association, [15][16][17][18] an inverse or a U-shaped association.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Some cohort studies have shown an increased risk of total stroke or ischemic stroke with elevating BMI, [8][9][10][11][12][13][14] which is in accord with the findings of the risk of ischemic stroke in our male subjects. On the other hand, other studies have found no association, [15][16][17][18] an inverse or a U-shaped association.…”
Section: Discussionsupporting
confidence: 89%
“…A similar independent association has been observed in other studies of stroke. 10,12,14 These findings, together with our present results, suggest a link between overweight/obesity and ischemic stroke independent of established risk factors. Some investigators have proposed that the increase in prothrombotic factors [27][28][29] and inflammatory markers, [30][31][32][33] and the enhancement of insulin resistance and metabolic syndrome 34 observed among overweight and obese individuals may have a role in their increased risk of ischemic stroke.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations